Economic Growth In Islamic Perspective: A Comparison Study Between Indonesia And Malaysia - M Fuad Hadziq (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
Economic policies cannot be avoided by political systems and legal certainty in a country. Islamic economic development is strongly influenced by state policies in determining the direction, form, and substance of the law. The most significant factor in a country's legal politics is in terms of institutional roles of government and regulatory products. The paper's purpose is to analyze the political implications of Islamic economic law in terms of institutions and legislation between Indonesia and Malaysia. The method of this research is qualitative descriptive with in-depth observation. The analysis makes tabulation, code, and categorization of several concepts, then concluded by inductive methods. As for the results of legal politics are very influential in the significant progress of Islamic economics in Indonesia and Malaysia. Indonesian Bank has made many infrastructure regulations and blueprints in the development of Islamic economics. Supervision through DSN and DPS, they have established rules, fatwas in the operations of financial institutions. On the side of the legislation, many laws have been issued in the development of Islamic economics. In Indonesia, some communities clash with the principles of the Pancasila state. Although they are not contradictory. The legalization of Islamic economic regulations is an effort to positively enforce Islamic law from the jurisprudence of Islamic madhhab in the context of Indonesia. Malaysia is more advanced in its Islamic economic development than Indonesia, even in the world. One of the progress was influenced by the Hadhari Islamic movement. He further built the infrastructure of Islamic economists, so that the private sector has more role in the institutional company. In terms of supervision, he established a committee Sharia and control in his field called the Sharia Advisory Council (SAC). Both of them collaborated with the Central bank Act or Bank Negara Malaysia with comprehensive legislation.